The Quality of Teaching Digitalization in Primary School Context and Its Relationship to Leadership and Work Motivation - Sulastri Sulastri; Nurkolis Nurkolis; Widya Kusumaningsih; Milagros Racacho Baldemor (Jurnal Pendidikan Progresif, 2024)
The Quality of Teaching Digitalization in Primary School Context and Its Relationship to Leadership and Work Motivation. Objectives: This research aims to determine the influence of principal leadership and teacher work motivation on the quality of digitalization of teaching. Methods: This research method is quantitative causal comparative with teacher and school principal participants. Population 403 people, research sample 200 people with simple random sampling. The instrument has passed the validity test, reliability test and prerequisite test. Hypothesis testing uses correlation tests and analysis of variance. Findings: The research results show that there is a positive influence of the principal's leadership on the quality of teaching digitalization, there is a positive influence of teacher work motivation on the quality of teaching digitalization, and there is a joint positive influence of the principal's leadership and teacher work motivation on the quality of teaching digitalization. Conclusion: It can be concluded that the results of this research reaffirm how important the role of school principal leadership and teacher work motivation is in realizing teaching quality. Keywords: digitalization school management, digitizing schools work, supportive leadership, intrinsic motivation, digital scholarship.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202474